Sentiment Analysis of the LinkedIn Application Using the Lexicon Based Meth¬od Based on Google Play Store Reviews - Meriska Defriani; Muhammad Rafi Muttaqin; Qonita Rizkiya Karima (RISTEC : Research in Information Systems and Technology, 2024)
LinkedIn is the largest professional network in the internet world. Useful for finding the right job, strengthening professional relationships, learning skills as needed for a successful career and having the opportunity to expand relationships. In this study, we will analyze the sentiment of android users towards one of the applications in the google play store, namely LinkedIn, through reviews in the google play store comments column. The research method is lexicon based using the vader sentiment library to determine the value of whether the sentence is in the positive, negative or neutral class. Based on the results of the percentage accuracy obtained that android users of the LinkedIn application on the google play store using the lexicon based method by utilizing the vader sentiment library, namely 56.56% for the positive sentiment class, 30.62% for the neutral sentiment class and 12.82% for the negative sentiment class. This shows that positive sentiment is greater than negative and neutral sentiment. Keywords : LinkedIn; google play store; lexicon based; library vader sentiment